2020
DOI: 10.1016/j.heliyon.2020.e05576
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics influence cultivable-bacteria composition in the meconium of Indonesian neonates

Abstract: Background Microbial colonization of a neonate's gastrointestinal tract has significant perinatal and lifetime health consequences. However, information regarding the profile of meconium microbiota in neonates and the influence of clinical parameters are lacking in the Indonesian population. This study aimed to preliminary investigate the profile of cultivable bacterial diversity of meconium isolated from neonates born at Cipto Mangunkusumo Hospital (CMH), Jakarta. The cultivable bacteria were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
2
2
0
1
Order By: Relevance
“…This study shows the development and diversity of the gut microbiome in 24 samples derived from the feces samples of eight preterm neonates born at CMH, Jakarta, at 3 different time points in early life. The analysis of gut microbiome development over the first week based on alpha and beta diversity in terms of relative abundance showed that for the 8 subjects providing 24 feces samples at the three time points, i.e., meconium, day 4 feces, and day 7 feces, Proteobacteria and Firmicutes were dominant at the phylum level, while at the genus level, unidentified Enterobacteriaceae were most abundant, as has been reported widely 1 , 6 , 7 , 9 , 10 , 29 34 . This result is similar to our previous study on cultivable bacteria from meconium from neonates born in CMH 9 .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This study shows the development and diversity of the gut microbiome in 24 samples derived from the feces samples of eight preterm neonates born at CMH, Jakarta, at 3 different time points in early life. The analysis of gut microbiome development over the first week based on alpha and beta diversity in terms of relative abundance showed that for the 8 subjects providing 24 feces samples at the three time points, i.e., meconium, day 4 feces, and day 7 feces, Proteobacteria and Firmicutes were dominant at the phylum level, while at the genus level, unidentified Enterobacteriaceae were most abundant, as has been reported widely 1 , 6 , 7 , 9 , 10 , 29 34 . This result is similar to our previous study on cultivable bacteria from meconium from neonates born in CMH 9 .…”
Section: Discussionsupporting
confidence: 63%
“…The analysis of gut microbiome development over the first week based on alpha and beta diversity in terms of relative abundance showed that for the 8 subjects providing 24 feces samples at the three time points, i.e., meconium, day 4 feces, and day 7 feces, Proteobacteria and Firmicutes were dominant at the phylum level, while at the genus level, unidentified Enterobacteriaceae were most abundant, as has been reported widely 1 , 6 , 7 , 9 , 10 , 29 34 . This result is similar to our previous study on cultivable bacteria from meconium from neonates born in CMH 9 . The microbiomes of meconium, as the first feces in this study, were relatively similar, with one subject showing a high abundance of the genus Ureaplasma and the rest showing a high abundance of Enterobacter.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…PCR dilakukan dengan kondisi denaturasi awal pada suhu 95 o C selama 5 menit, denaturasi pada suhu 94 o C selama 30 detik, penempelan pada suhu 63 o C selama 30 detik, pemanjangan pada suhu 68 o C selama 40 detik, dan pemanjangan akhir pada suhu 68 o C selama 6 menit. Tahap denaturasi hingga pemanjangan diulang sampai 30 siklus (13) .…”
Section: Pemilihan Kit Ekstraksiunclassified